Synergistic Interaction of Histone Deacetylase 6- and MEK-Inhibitors in Castration-Resistant Prostate Cancer Cells - Corno, Cristina; Arrighetti, Noemi; Ciusani, Emilio; Corna, Elisabetta; Carenini, Nives; Zaffaroni, Nadia; Gatti, Laura; Perego, Paola (Frontiers in Cell and Developmental Biology, 2020)
In spite of new knowledge on prostate cancer molecular landscape, this has been only partially translated to the therapeutic setting. The activation of Ras/Mitogen-activated protein kinase (MAPK) signaling plays an important role in progression of prostate cancer in which deregulation of histone deacetylases (HDAC) is frequent. Based on the notion that HDAC inhibitors may reactivate the expression of genes favoring cell response to drugs, the aim of this study was to investigate the interaction between the HDAC6-specific inhibitor ricolinostat (ACY1215) and the MEK-inhibitor selumetinib (AZD6244) to identify effective combinations in prostate cancer models. Using cell lines exhibiting differential activation of survival pathways (PC3, DU145, 22Rv1) and following different treatment schedules, a synergistic interaction was observed in all cell models, the drug combination being particularly effective in 22Rv1 cells. Marginal levels of apoptosis were observed in PC3 cells after combined treatment, whereas higher levels were achieved in DU145 and 22Rv1 cells. RNAi-mediated knowckdown of HDAC6 in selumetinib-treated 22Rv1 cells resulted in increased apoptosis. Combined treatment suppressed the constitutively deregulated survival pathways in all cell lines. A decrease of androgen receptor (AR)-dependent gene (KLK2, DUSP1) mRNA levels was observed in 22Rv1 treated cells, associated with increased AR cytoplasmatic expression, suggesting AR signalling downregulation, not involving Hsp90 acetylation. When a taxane was used in combination with AZD6244 and ACY1215 by a simultaneous schedule, a synergistic cytotoxic effect together with increased apoptosis was evidenced in all cell models. These results support a rational use of targeted agents to improve prostate cancer cell apoptotic response.